The Long Term Role of Anxiety Sensitivity and Experiential Avoidance on Pain Intensity, Mood, and Disability among Individuals in a Specialist Pain Clinic - S. Mehta; D. Rice; S. Janzen; J. Serrato; H. Getty; A. P. Shapiro; P. Morley-Forster; K. Sequeira; R. W. Teasell (Pain Research and Management)
Background. Anxiety sensitivity (AS) and experiential avoidance (EA) have been shown to have an interactive effect on the response an individual has to chronic pain (CP) potentially resulting in long term negative outcomes. Objective. The current study attempted to (1) identify distinct CP subgroups based on their level of EA and AS and (2) compare the subgroups in terms of mood and disability. Methods. Individuals with CP were recruited from an academic pain clinic. Individuals were assessed for demographic, psychosocial, and personality measures at baseline and 1-year follow-up. A cluster analysis was conducted to identify distinct subgroups of patients based on their level of EA and AS. Differences in clinical outcomes were compared using the Repeated Measures MANOVA. Results. From a total of 229 participants, five clusters were formed. Subgroups with lower levels of AS but similar high levels of EA did not differ in outcomes. Mood impairment was significantly greater among those with high levels of EA compared to lower levels (p<0.05). Significant improvement in disability (p<0.05) was only seen among those with lower levels of EA and AS. Conclusions. This cluster analysis demonstrated that EA had a greater influence on mood impairment, while both EA and AS levels affected disability outcomes among individuals with CP.